Deep sea 2003 : (FAO, 2006)
This second volume of the Proceedings of the Conference on the Governance and Management of Deep-sea Fisheries, held in Queenstown, New Zealand, from 1 to 5 December 2003, contains papers developed from many of the presentations in the Poster Session of the Conference. Poster-papers presented in this volume address issues of deep-sea oceanography, ecology, fisheries management and governance. The second part of this volume of the Proceedings contains papers that were presented at the workshops held in Dunedin, New Zealand, from 27 to 29 November, just prior to Deep Sea 2003. There were four workshops that addressed the topics of: Assessment and management of deepwater fisheries; Management of small-scale deep-sea fisheries; Conservation and management of deepwater chondrichthyan fishes; and, Bioprospecting in the high seas.